2015
DOI: 10.1159/000369685
|View full text |Cite
|
Sign up to set email alerts
|

The OPN Gene Polymorphism Confers the Susceptibility and Response to Ara-C Based Chemotherapy in Chinese AML Patients

Abstract: Aim: To investigate the possible association between the Osteopontin (OPN) gene polymorphisms and the susceptibility and chemotherapy response of acute myeloid leukemia patients. Methods: A total of 381 patients with de nova AML and 430 healthy controls were enrolled. All patients received Ara-C-based standard induction chemotherapy regimens, and the treatment response was evaluated. Several polymorphisms in the human OPN encoding gene have been identified. The OPN) gene polymorphisms at 3 loci, namely, -156 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…OPN was detected with considerable polymorphism, recent study found that the -443C>T polymorphism of OPN was able to serve for susceptibility as well as chemotherapy response of AML [29]. OPN is thought to contain bioactive regions on its surface, along with its RGD sequences, that can exhibit multiple biological functions, including the activation of some regulatory and structural proteins when connecting with its integrin receptors [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…OPN was detected with considerable polymorphism, recent study found that the -443C>T polymorphism of OPN was able to serve for susceptibility as well as chemotherapy response of AML [29]. OPN is thought to contain bioactive regions on its surface, along with its RGD sequences, that can exhibit multiple biological functions, including the activation of some regulatory and structural proteins when connecting with its integrin receptors [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most studied OPN single-nucleotide polymorphism is rs11730582, whose −443 CC genotype has been associated with higher expression of OPN and increased cancer risk in acute myeloid leukemia, glioma, and papillary thyroid cancer. Interestingly, in other tumors such as hepatocellular carcinoma (HCC), breast cancer, nasopharyngeal carcinoma, and melanoma, the −443 TT genotype, rather than the C allele, correlates with increased expression of OPN [5056]. In this regard, it has been proposed that the proto-oncogene c-Myb mediates induction of OPN expression levels from the C allele in some tumors, whereas in other malignancies, a yet unidentified transcription factor could activate transcription of OPN from the T allele [56].…”
Section: Opn General Featuresmentioning
confidence: 99%
“…In spite of recent improvement in therapeutic strategies, AML remains an incurable disease for majority of patients [30,32,33]. Predominantly, development of chemoresistance is a major bottleneck limiting the therapeutic efficacy in AML therapy [34].…”
Section: Discussionmentioning
confidence: 99%